Burning Down The House : Gwangju Biennale 2014 - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2014)
Exhibition Guide. Artists include: Ruanne Abou-Rahme & Basel Abbas, Hamed Abdalla, Abbas Akhavan, Lubaina Himid, Huma Mulji, Anwar Jalal Shemza, Nil Yalter, Akram Zaatari, Mrinalini Mukherjee
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions